The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1464-410x.2011.10048.x
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of repeat transrectal ultrasonography guided prostate biopsies with local anaesthesia

Abstract: OBJECTIVE • To measure patient discomfort associated with transrectal ultrasonography guided prostate biopsy (TRUSPB) performed with periprostatic local anaesthetic (LA) infiltration and to document agreement to possible repeat biopsy, as a recent audit showed that 86% of Australian urologists performed prostate biopsies using sedation or general anaesthesia (GA), which implies many urologists think patients are unwilling to tolerate the procedure under LA block and/or may refuse a repeat procedure. PATIENTS A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 17 publications
4
19
2
Order By: Relevance
“…39 In a prospective study of patients who had previously undergone transrectal prostate biopsy with general anesthesia and had a repeat biopsy performed with local anesthesia, 98% would agree to local anesthesia for any future biopsies. 36 Although our study design precludes a systematic, formal assessment of patient attitudes toward interpolated flap repair performed under local anesthesia, our experience suggests that patients tolerate this procedure well in these settings.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…39 In a prospective study of patients who had previously undergone transrectal prostate biopsy with general anesthesia and had a repeat biopsy performed with local anesthesia, 98% would agree to local anesthesia for any future biopsies. 36 Although our study design precludes a systematic, formal assessment of patient attitudes toward interpolated flap repair performed under local anesthesia, our experience suggests that patients tolerate this procedure well in these settings.…”
Section: Discussionmentioning
confidence: 97%
“…A comparison of inguinal hernia repair under local or general anesthesia showed that patients receiving local anesthesia experienced significantly lower postoperative analgesic requirements, lower incidence of urinary retention, shorter duration of hospital stay, and greater satisfaction . In a prospective study of patients who had previously undergone transrectal prostate biopsy with general anesthesia and had a repeat biopsy performed with local anesthesia, 98% would agree to local anesthesia for any future biopsies . Although our study design precludes a systematic, formal assessment of patient attitudes toward interpolated flap repair performed under local anesthesia, our experience suggests that patients tolerate this procedure well in these settings.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous feasibility study examining Penthrox for TRUS biopsy found that the cost of anaesthetic staff alone for a single TRUS‐guided biopsy at The Alfred Hospital in Melbourne in 2011 was A$421 . The cost of anaesthetic staff for the same procedure in Sydney has been calculated to be about A$399 . In contrast, the Penthrox inhaler costs A$39 per unit and 2% lignocaine for injection is less than A$0.50 per millilitre.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the patients tolerated the procedure very well, and 97.5% of the patients stated that they would accept this method again if another PBx was required. 23 Even rare, there may be hemorrhagic and infectious complications after the PPNB, as is the case for patients who do not have PPNB. Some authors reported bacteriuria, fever, and complications requiring hospitalization after the anesthetic injection.…”
Section: Resultsmentioning
confidence: 99%